An enhanced traffic separation mechanism to support real-time communication in IEEE 802.11e networks - Ricardo Moraes (2006)
In this paper, a new traffic separation mechanism is proposed forIEEE 802.11e networks. Such Traffic Separation Mechanism (TSm) allows thecoexistence of CSMA default stations with real-time stations in the samenetwork domain. A station implementing the proposed TSm scheme has thesame operating behavior as a default IEEE 802.11e network station, except inwhat concerns the evaluation of the backoff delay. A station implementing theTSm scheme eventually imposes the transfer of its messages prior to thetransfer of any lower priority message.